Exploring the Moderation of Meaning in Life in Barriers and Coping Efficacy Among Women. (October 2020) - Marks, Laura Reid; Tate, Kevin A.; Taylor, Jennifer M.
In this study, we sought to extend social cognitive career theory and examined the links among perceptions of career and educational barriers, coping self-efficacy, and meaning in life in a diverse sample of women. Five hundred and seventy-nine female participants were recruited using Amazon Mechanical Turk where they were asked to complete an online survey. Our analyses revealed a significant negative relationship between educational and career barriers and coping self-efficacy. When controlling for social class, a presence of and a search for meaning in life were not significant moderators of the association between educational and career barriers and coping self-efficacy. However, when not controlling for social class, a presence of a meaning for life did significantly moderate the association between educational barriers and coping self-efficacy. Implications of these findings for counselors working with women on their career development and for future research are discussed.